Sustainable land management through market oriented commodity development: Case studies from Ethiopia - Gebremedhin, Berhanu; Woldewahid, G.; Dessalegn, Yigsaw; Gebey, T.; Teka, W. (International Livestock Research Institute, 2010)
Land degradation has been identified as severe environmental problem in Ethiopia, especially since the early 1970s. Because there is significant degradation on cultivated lands in Ethiopia, there is potentially high payoff to addressing degradation in the country. In this paper we focus mainly on the effect of short-term benefits to farmers and the explicit considerations of the linkages between natural resource management and market-oriented commodity development on the adoption and scaling out of sustainable land management practices. We hypothesize that linking natural resource management with market-oriented commodity development enhances sustainable land management by providing farmers with short-term benefits. We test this hypothesis with analysis of case studies of four districts in Ethiopia. Two of the case studies deal with the linkage between grazing land development and market-oriented livestock development, and the other two deal with the linkage between conservation agriculture and market-oriented crop production. Results indicate that, indeed, direct linkages of natural resource management with market-oriented commodity development that have profitable market opportunities can enhance sustainable land management. Results imply that participatory approaches to the appraisal of community resources, identification and prioritization of key constraints of commodity development, and implementation of interventions greatly facilitate adoption and scaling out of interventions.